It is: 9a-a-a = 7a
2a+5a+9a = 16a
-14 + 9a = 389a = 52a = 52/9 or 5.78
-21 = 9a - 15 - 3a -6 = 6a -1 = a
4a - 2.1 = 9a + 5.4 4a - 9a = 5.4 +2.1 -5a = 7.5 -a = 1.5 a = -1.5
It is: 9a-a-a = 7a
9a+21 3(3a+7)
2a+5a+9a = 16a
-14 + 9a = 389a = 52a = 52/9 or 5.78
12a + 6b + 9a + 14b =(12a + 9a) + (6b + 14b) =21a + 20b
-21 = 9a - 15 - 3a -6 = 6a -1 = a
-a^2- 9a - 18 = 0 -(a^2 + 9a + 18) = 0 -(a + 6)(a + 3) = 0
9a + 4a = 26 13a = 26 a = 26/13 a = 2
4a - 2.1 = 9a + 5.4 4a - 9a = 5.4 +2.1 -5a = 7.5 -a = 1.5 a = -1.5
a is equal to 1.
a= -4
-6 -9a = 16 : Add 6 to both sides -9a = 22 : Multiply both sides by -1 9a = -16 : Divide both sides by 9 a = -16/9 = -17/9